Not quite a telescoping sum (2)

Calculus Level 4

n = 0 [ 1 12 n + 1 + 1 12 n + 5 1 12 n + 7 1 12 n + 11 ] \displaystyle \sum_{n=0}^{\infty} \left[\frac{1}{12n+1}+\frac{1}{12n+5}-\frac{1}{12n+7}-\frac{1}{12n+11} \right] can be written in the form π a \dfrac{\pi}{a} .

What is the value of a a ?


The answer is 3.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Guilherme Niedu
May 4, 2020

S = n = 0 [ 1 12 n + 1 + 1 12 n + 5 1 12 n + 7 1 12 n + 11 ] \large \displaystyle S = \sum_{n=0}^{\infty} \left [ \frac{1}{12n+1} + \frac{1}{12n+5} - \frac{1}{12n+7} - \frac{1}{12n+11} \right ]

S = n = 0 [ 1 12 n + 1 1 12 n + 3 + 1 12 n + 5 1 12 n + 7 + 1 12 n + 9 1 12 n + 11 ] + n = 0 [ 1 12 n + 3 1 12 n + 9 ] \large \displaystyle S = \sum_{n=0}^{\infty} \left [ \frac{1}{12n+1} - \frac{1}{12n+3} + \frac{1}{12n+5} - \frac{1}{12n+7} + \frac{1}{12n+9} - \frac{1}{12n+11} \right ] + \sum_{n=0}^{\infty} \left [ \frac{1}{12n+3} - \frac{1}{12n+9} \right ]

S = n = 0 [ ( 1 ) n 2 n + 1 ] + 1 3 n = 0 [ 1 4 n + 1 1 4 n + 3 ] \large \displaystyle S = \sum_{n=0}^{\infty} \left [ \frac{(-1)^n}{2n+1} \right ] + \frac13 \sum_{n=0}^{\infty} \left [ \frac{1}{4n+1} - \frac{1}{4n+3} \right ]

S = n = 0 [ ( 1 ) n 2 n + 1 ] + 1 3 n = 0 [ ( 1 ) n 2 n + 1 ] \large \displaystyle S = \sum_{n=0}^{\infty} \left [ \frac{(-1)^n}{2n+1} \right ] + \frac13 \sum_{n=0}^{\infty} \left [ \frac{(-1)^n}{2n+1} \right ]

S = 4 3 n = 0 [ ( 1 ) n 2 n + 1 ] \large \displaystyle S = \frac43 \sum_{n=0}^{\infty} \left [ \frac{(-1)^n}{2n+1} \right ]

By the Maclaurin Series of arctan \arctan

S = 4 3 arctan ( 1 ) \large \displaystyle S = \frac43 \arctan(1)

S = π 3 \color{#20A900} \boxed {\large \displaystyle S = \frac{\pi}{3} }

So:

a = 3 \color{#3D99F6} \boxed {\large \displaystyle a = 3}

S = n = 0 ( 1 12 n + 1 + 1 12 n + 5 1 12 n + 7 1 12 n + 11 ) = 1 + 1 5 1 7 1 11 + 1 13 + 1 17 1 19 1 23 + = 1 1 3 + 1 5 1 7 + 1 9 1 11 + 1 13 1 15 + + ( 1 3 1 9 + 1 15 1 21 + 1 27 1 33 + ) = 1 1 3 + 1 5 1 7 + 1 9 1 11 + 1 13 1 15 + + 1 3 ( 1 1 3 + 1 5 1 7 + 1 9 1 11 + ) = 4 3 ( 1 1 3 + 1 5 1 7 + 1 9 1 11 + 1 13 1 15 + ) = 4 3 tan 1 ( 1 ) = 4 3 × π 4 = π 3 \begin{aligned} S & = \sum_{n=0}^\infty \left(\frac 1{12n+1} + \frac 1{12n+5} - \frac 1{12n+7} - \frac 1{12n+11} \right) \\ & = 1 + \frac 15 - \frac 17 - \frac 1{11} + \frac 1{13} + \frac 1{17} - \frac 1{19} - \frac 1{23} + \cdots \\ & = 1 - \frac 13 + \frac 15 - \frac 17 + \frac 19 - \frac 1{11} + \frac 1{13} - \frac 1{15} + \cdots + \left( \frac 13 - \frac 19 + \frac 1{15} - \frac 1{21} + \frac 1{27} - \frac 1{33} + \cdots \right) \\ & = 1 - \frac 13 + \frac 15 - \frac 17 + \frac 19 - \frac 1{11} + \frac 1{13} - \frac 1{15} + \cdots + \frac 13 \left(1 - \frac 13 + \frac 15 - \frac 17 + \frac 19 - \frac 1{11} + \cdots \right) \\ & = \frac 43 \left(1 - \frac 13 + \frac 15 - \frac 17 + \frac 19 - \frac 1{11} + \frac 1{13} - \frac 1{15} + \cdots \right) \\ & =\frac 43 \tan^{-1} (1) = \frac 43 \times \frac \pi 4 = \frac \pi 3 \end{aligned}

Therefore, a = 3 a=\boxed 3 .

Naren Bhandari
May 5, 2020

n = 0 ( 1 12 n + 1 + 1 12 n + 5 1 12 n + 7 1 12 n + 11 ) = n = 0 ( 1 12 n + 5 1 12 n + 7 ) + n = 0 ( 1 12 n + 1 1 12 n + 11 ) = 1 12 n = 0 ( 1 n + 5 12 1 n + 7 12 ) + 1 12 n = 0 ( 1 n + 1 12 1 n + 11 12 ) = 1 12 ( ψ 0 ( 7 12 ) ψ 0 ( 5 12 ) + ψ 0 ( 11 12 ) ψ 0 ( 1 12 ) ) \sum_{n=0}^{\infty}\left(\frac{1}{12n+1}+\frac{1}{12n+5}-\frac{1}{12n+7}-\frac{1}{12n+11}\right)=\sum_{n=0}^{\infty}\left(\frac{1}{12n+5}-\frac{1}{12n+7}\right) +\sum_{n=0}^{\infty}\left(\frac{1}{12n+1}-\frac{1}{12n+11}\right) \\=\frac{1}{12}\sum_{n=0}^{\infty}\left(\frac{1}{n+\frac{5}{12}}-\frac{1}{n+\frac{7}{12}}\right) +\frac{1}{12}\sum_{n=0}^{\infty}\left(\frac{1}{n+\frac{1}{12}}-\frac{1}{n+\frac{11}{12}}\right)=\frac{1}{12}\left(\psi^0\left(\frac{7}{12}\right)-\psi^0\left(\frac{5}{12}\right)+\psi^0\left(\frac{11}{12}\right)- \psi^0\left(\frac{1}{12}\right)\right) Using the relation ψ ( 1 z ) ψ ( z ) = π cot ( π z ) \psi(1-z)-\psi(z)= \pi\cot(\pi z) gives us π 12 ( cot ( 5 π 12 ) + cot ( π 12 ) ) = 4 π 12 = π 3 \frac{\pi}{12}\left(\cot\left(\frac{5\pi}{12}\right)+\cot\left(\frac{\pi}{12}\right)\right)=\frac{4\pi}{12}=\frac{\pi}{3} Since cot A + cot B = sin ( A + B ) sin A sin B \cot A +\cot B=\frac{\sin(A+B)}{\sin A\sin B} putting A = π 12 A=\frac{\pi}{12} and B = 5 π 12 B=\frac{5\pi}{12} . We have cot ( π 12 ) + cot ( 5 π 12 ) = sin ( π 2 ) sin ( π 12 ) sin ( 5 π 12 ) = 1 sin ( π 12 ) cos ( π 12 ) = 2 sin ( π 6 ) = 4 \cot\left(\frac{\pi}{12}\right)+\cot\left(\frac{5\pi}{12}\right)=\frac{\sin\left(\frac{\pi}{2}\right)}{\sin\left(\frac{\pi}{12}\right)\sin\left(\frac{5\pi}{12}\right)}=\frac{1}{\sin\left(\frac{\pi}{12}\right)\cos\left(\frac{\pi}{12}\right)}\\=\frac{2}{\sin\left(\frac{\pi}{6}\right)}=4

What is the name of that function?

Chris Sapiano - 1 year, 1 month ago

Log in to reply

It is the Digamma Function

Aaghaz Mahajan - 1 year, 1 month ago

digamma @Chris Sapiano

Ajay Anand Dwivedi - 10 months, 4 weeks ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...